Reductive dechlorination of gamma-hexachlorocyclohexane using Fe-Pd bimetallic nanoparticles - Nagpal, Varima; Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Journal of Hazardous Materials, 2010)
Nanoscale Fe-Pd bimetallic particles were synthesized and used for degradation of lindane (gamma-hexachlorocyclohexane) in aqueous solution. Batch studies showed that 5 mg/Lof lindane was completely dechlorinated within 5 min at a catalyst loading of 0.5 g/L and the degradation process followed first-order kinetics. GC-MS analysis in corroboration with GC-ECD results showed the presence of cyclohexane as the final degradation product. The proposed mechanism for the reductive dechlorination of lindane involves Fe corrosion-induced hydrogen atom transfer from the Pd Surface. The enhanced degradation efficiency of Fe-Pd nanoparticles is attributed to: (1) high specific surface area of the nanoscale metal particles (60 m(2)/g), manyfold greater that of commercial grade micro- or milli-scale iron particles (similar to 1.6 m(2)/g); and, (2) increased catalytic reactivity due to the presence of I'd on the Surface. Recycling and column studies showed that these nanoparticles exhibit efficient and sustained catalytic activity. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bimetallic; Cyclohexane; Degradation; kinetics; Lindane; Nanoparticles

Etherification of biomass-derived glycerol to oxygenated fuel additives using dodecatungstophosphoric-silica-supported catalyst: characterization and kinetic studies - Magar, Subhash B.; Kapoor, Ashish; Jana, Sumit Kumar; Pal, Dan Bahadur; Rode, Chandrashekhar V. (Biomass Conversion and Biorefinery, 2023)
Commercial biodiesel production is becoming popular due to its sustainability and reduced greenhouse gas emissions in comparison to fossil fuels. Biodiesel production involves the co-generation of crude glycerol that is not directly viable. Valorization of glycerol is essential from techno-economic perspective to achieve goals of circular economy. In this study, the glycerol etherification was carried out using tert-butyl alcohol in presence of dodecatungstophosphoric/silica (DTP/SiO2) catalyst for production of tert-butyl glycerol ethers that can be used as fuel additives. A series of DTP/SiO2 catalysts were prepared with various compositions by impregnating heteropoly acids (HPA, H3PW12O40). The product analysis was performed to monitor mono-, di-, and tri-tert-butyl glycerol ethers. The kinetic studies were conducted based on Langmuir-Hinshelwood model. The rate constants were determined from experimental data by regression analysis. The catalysts were characterized by X-ray diffraction, SEM/EDX, and thermogravimetric analysis. Varying DTP loadings resulted in different catalytic activities. Activation energy (38.23 kJ/mol), activation enthalpy (25.94 kJ/mol), activation entropy (-163.8 J/mol/K), and Gibbs free energy of activation (88.67 kJ/mol) were attained for DTP/SiO2 (20%) catalyst that exhibited the best selectivity for di-tert-butyl glycerol ethers.
Keywords: Catalytic; etherification; fuel additives; Hinselwood; Impregnation; kinetics; Langmuir